DETERMINANTS OF SME SUCCESS OR FAILURE IN FRONTIER MARKETS (International Journal of Banking and Finance, 2023)
SME competitiveness, financial stability, and and its continuity as a going concern are important considerations for companystakeholders. This research is utilizing logistic regression to examine the determinants of SME business success or failure in Cambodia. A total of 314 successful and 78 failing SMEs were examined. Information was gathered through a survey questionnaire that had been previously validated in various countries based on the financial and non-financial information of SMEs. The study found that four factors, namely the owner’s education level, owner’s marketing skills, customer complaints, and the age of the business were important in determining the success or failure of SMEs. The predictive accuracy of the model was 95.5 percent, with an R-square estimation of 64 percent. Policymakers can use the results of this study to prepare and train aspirant entrepreneurs and current SME proprietors to keep proper records and maintain financial control, and develop marketing and other skills to assist their businesses to succeed. The findings can provide insights for entrepreneurs, especially with respect to efficient resource allocations that may help avert or lessen the rate of failure among SMEs. The findings can also help strengthen the SME sector in Cambodia, by providing more employment opportunities, assisting in better income distribution, and eventually leading to long-term prosperity and competitiveness.